Anak Agung Sagung Istri Salshayna Pramesti - Anak Agung Sagung Istri Salshayna Pramesti; I Ketut Suryanawa (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2024)
This study examines the influence of company size, profitability, leverage, institutional ownership, and public ownership on Corporate Social Responsibility (CSR) disclosure among consumer non-cyclical companies listed on the Indonesia Stock Exchange during the 2021-2022 period. The research is contextualized by the Financial Services Authority Circular Letter No. 16/SEOJK.04/2021, which outlines regulatory expectations for CSR activities. A total of 160 companies were selected through purposive sampling for non-participant observation analysis. Contrary to expectations, the findings reveal that company size, leverage, institutional ownership, and public ownership do not significantly influence CSR disclosure. However, profitability emerges as the only factor with a positive impact on CSR disclosure. This highlights the need for a deeper understanding of the factors driving CSR engagement in the region and suggests that profitable companies may be more likely to engage in CSR activities, potentially due to better resources or a strategic approach to stakeholder engagement.